Impact Of A Successfully Synchronized Supply Chain Management As A Competitive Edge In The Electronic Industry - Kiat Soon, Ng (2008)
The purpose of this research is to provide a comprehensive clarification with regards to the numerous factors of concern that has critically challenged the electronic industry in their aim to implement a well synchronized supply chain management as a tool to stay competitive in the global market. In the other hand, the opportunities or advantage of a well synchronized supply chain management will be highlight in this research paper. At the same time, this research also tends to investigate the opinion of the electronic industry regarding supply chain management practices.